Development and implementation of evidence-based laboratory safety management tools for a public health laboratory. (August 2019) - Keckler, M.S.; Anderson, K.; McAllister, S.; Rasheed, J.K.; Noble-Wang, J.
Graphical abstract: Highlights: Data on perceived hazards in a federal public health laboratory. Practical survey tool for collecting a broad range of data for laboratory risk management. Practical method for stratifying the risk of microorganisms handled in a BSL-2 laboratory. Practical three-dimensional risk analysis method to prioritize interventions. Inferential method to assess safety intervention effectiveness. Abstract: We developed an evidence-based continuous quality improvement (CQI) cycle for laboratory safety as a method of utilizing survey data to improve safety in a public health laboratory setting. Expert Opinion : The CQI cycle begins with the solicitation of laboratory staff input via an annual survey addressing potential chemical, physical and radiological hazards associated with multiple laboratory activities. The survey collects frequency, severity and exposure data related to these activities in the context of the most pathogenic organisms handled at least weekly. Gap Analysis: Step 2 of the CQI cycle used survey data to identify areas needing improvement. Typically, the traditional two-dimensional risk assessment matrix is used to prioritize mitigations. However, we added an additional dimension – frequency of exposure – to create three-dimensional risk maps to better inform and communicate risk priorities. Mitigation Measures: Step 3 of the CQI cycle was to use these results to develop mitigations. This included evaluating the identified risks to determine what risk control measures (elimination, substitution, engineering, administrative or PPE) were needed. In the 2016 iteration of the CQI cycle described here, all mitigations were based on administrative controls. Evaluation and Feedback: The last step of the CQI cycle was to evaluate the inferred effects of interventions through subsequent surveys, allowing for qualitative assessment of intervention effectiveness while simultaneously restarting the cycle by identifying new hazards. Here we describe the tools used to drive this CQI cycle, including the survey tool, risk analysis method, design of interventions and inference of mitigation effectiveness.